Peningkatan Produksi, Pencatatan Kartu Persediaan Dan Pemasaran Sale Pisang UD Sumber Alam Buana di Kabupaten Banyuwangi - Dilla Cattleyana; Adytira Rachman (LOYALITAS: Jurnal Pengabdian Kepada Masyarakat, 2019)
Micro, Small and Medium Enterprises (UMKM) has an important role in the Indonesian economy, one of which can help the per capita income of the Indonesian state, especially in Banyuwangi Regency, as well as in the UM Banana Sale UD UD. Sumber Alam Buana, located at the eastern end of the island of Java, precisely in Banyuwangi. The UMKM is one of Banyuwangi's original typical food businesses from Ambon banana raw material, bearing in mind that typical food is identical to souvenirs (souvenirs) when visiting Banyuwangi, certainly not forgetting to bring and share them with you. However, there are problems in the field of production of UD Banana Banana UD, namely the low production capacity of processing banana raw materials because it still uses a cutting knife and the appropriate method has not been applied to record raw materials or finished goods so that the owner is less able to control the cycle of raw materials or finished goods. While in the marketing sector it is still conventional to be entrusted in a gift shop so that it can only wait for whether the product is sold or vice versa. The solution to the development activities of UMKM Sale Banana UD Sumber Alam Buana includes counseling and training using a banana chopper tool that is more efficient than a knife that has been used to chop banana raw materials. Whereas in terms of recording to help partners to control raw material inventory and finished goods efficiently and effectively, the need for training knowledge and assistance to owners and employees using a perpetual method stock card (inventory). To expand market share that has demanded the use of technology, training is held to make e-mail as a portal to access several e-commerce websites and to open online stores through social media such as Facebook and others. The results achieved in the Community Service program are the development of this business in terms of increasing production capacity, managing raw materials, expanding markets and increasing income.